Acid‐Catalyzed Regiodivergent Annulation of 4‐Hydroxycoumarins with Isoprene: Entry to Pyranocoumarins and Pyranochromones. Issue 38 (24th September 2019) - Li, Ying; Hu, Yan‐Cheng; Zheng, Hao; Ji, Ding‐Wei; Cong, Yu‐Feng; Chen, Qing‐An
Abstract : An acid‐catalyzed regiodivergent formal [3+3] annulation of 4‐hydroxycoumarins with isoprene is developed. A variety of pyranocoumarins were obtained exclusively in the presence of strong Brønsted acid, while varying to Lewis acid delivered pyranochromones as main products. The protocol also features high atom‐economy, wide substrate scope, easy scale‐up, and good applications in natural product synthesis. Abstract : An acid‐catalyzed regiodivergent annulation of biomass‐derived 4‐hydroxycoumarins with isoprene is developed, providing a facile access to pyranocoumarins and pyranochromones.